Systematic comparison of sporadic and syndromic pancreatic islet cell tumors - Erlic, Zoran; Ploeckinger, Ursula; Cascon, Alberto; Hoffmann, Michael M.; Duecker, Laura von; Winter, Aurelia; Kammel, Gerit; Bacher, Janina; Sullivan, Maren; Isermann, Berend; Fischer, Lars; Raffel, Andreas; et al. (Endocrine related cancer, 2010)
Pancreatic islet cell tumors (ICTs) occur as sporadic neoplasias or as a manifestation of multiple endocrine neoplasia type 1 (MEN1) and von Hippel-Lindau disease (VHL). Molecular classification of ICTs is mandatory for timely diagnosis and surveillance. Systematic comparison of VHL-ICTs and sporadic ICTs has been lacking. Our registry-based approaches used the German NET-Registry with 259 patients with neuroendocrine tumors (NETs), who were primarily diagnosed with NETs, and the German VHL-Registry with 485 molecular genetically confirmed patients who had undergone magnetic resonance imaging or computed tomography of the abdomen. All patients provided blood DNA for testing of the MEN1 and VHL genes for intragenic mutations and large deletions. In the NET-Registry, 9/101 patients (8.9%) with ICTs had germline mutations, 8 in MEN1 and 1 in VHL. In the VHL-Registry, prevalence of NETs was 52/487 (10.6%), and all were ICTs. Interestingly, of those with VHL p.R167W, 47% developed ICTs, compared to 2% of those with p.Y98H. In total, there were 92 truly sporadic, i.e. mutation-negative ICT patients. Comparing these with the 53 VHL-ICT patients, the statistically significant differences were predominance of female gender (P=0.01), multifocal ICTs (P=0.0029), and lower malignancy rate (P<0.001) in VHL-ICTs compared to sporadic cases. VHL was prevalent in <0.5% of NETs, while NETs occur in ∼10% of VHL, virtually exclusively as ICTs, which are rarely the first presentation. Patients with NETs should not be subjected to genetic testing of the VHL gene, unless they have multifocal ICTs, other VHL-associated tumors, and/or a family history for VHL.
Gesehen am 27.03.2023